Structure and activity study of tripeptide IRW in TNF-α induced insulin resistant skeletal muscle cells. Issue 7 (22nd March 2022) - Jiang, Xu; Wu, Jianping
Abstract : IRW was found to improve TNF-α induced insulin resistance. IRW analog IRA and derivative IR reversed the increased tyrosine residue of IRS and decreased serine residue of IRS induced by TNF-α. Thus, IRW, IR and IRA improved the GLUT4 translocation. Abstract : Egg white protein ovotransferrin derived peptide IRW (Ile-Arg-Trp) was found to improve tumor necrosis factor alpha (TNF-α) or angiotensin II induced insulin resistance in L6 cells. Our recent study further showed that this peptide can improve glucose tolerance in high fat diet fed C57BL/6 mice. However, the structural requirements of IRW, especially the significance of each amino acid residue of IRW, is unknown. The study was aimed to investigate the structure and activity relationships of IRW in TNF-α induced insulin resistance L6 cells. The peptides were designed to determine the significance of individual amino acids in IRW using alanine scanning (replacing one amino acid at one time), the order of the peptide sequence and the constituting elements of IRW. Among the tested peptides and amino acids, only IRA and IR showed the same effects as that of IRW: enhanced glucose uptake, improvement in the impaired insulin signaling pathway and increased glucose transporter protein 4 (GLUT4) translocation in TNF-α treated L6 myotubes. This study demonstrated that C-terminal W is not essential to the activity of IRW. Further study is necessary to establish if IR and IRA show similar effects to that of IRW in vivo .